The Effect of Parenting Training on the Ability of Parenting Styles for Children in Ciwareng Village, Purwakarta Regency, Indonesia - Ningsih, Eka Prihatin (Arkus, 2024)
Parenting is one of the important factors that influences children's development. The right parenting style can help children grow and develop into healthy and prosperous individuals. However, not all parents have good parenting skills. Parenting training can be an effort to improve parents' parenting skills. This research aims to determine the effect of parenting training on parents' parenting skills towards children in Ciwareng Village, Purwakarta Regency, Indonesia. This research uses quantitative methods with a pre-posttest control group design. The research sample was 60 parents who had children aged 6-12 years. The experimental group was given parenting training for 6 meetings, while the control group was given no training. The research results show that parenting training has a significant influence on parents' parenting abilities. The experimental group that received parenting training showed greater improvements in parenting abilities compared to the control group.